Analysis of the earthen architectural heritage in Piedmont (northern Italy): typologies, construction techniques and materials (Gremium, 2020)
Piedmont is characterized by the presence of numerous earthen buildings mainly concentrated in the province of Alessandria. Studies conducted over the last decade, however, have shown the presence of interesting examples of these buildings also in the provinces of Asti, Torino, Biella and Cuneo. They are generally two-storied rural constructions, built with both fired bricks (for the bearing structures) and adobe (for internal and external walls).